COVID-19 Unintended Effects on Breast Cancer in Italy After the Great Lockdown - Oldani, Chiara; Vanni, Gianluca; Buonomo, Oreste Claudio (Frontiers in Public Health, 2020)
Italy introduced social distancing measures, which limited the spread of COVID-19; all the non-life-threatening treatments have been temporarily suspended, including screening programs. This decision leads to unintended effects on the ability to detected neoplasia in their first stages. Possible future outcomes of the ability to detect new breast cancer cases based on two alternative scenarios show that the reduction in organized screening activities will limit the ability to detect no less than 3.43% of the new cases; the economic crisis will reduce voluntary screening, increasing the undetected new cases up to 11.73%. Cases diagnosed with delay will show up in their advanced stage along with unknown effects on mortality and health care costs. Global health care policies should be implemented to counterbalance these adverse effects.